2022
DOI: 10.1177/07334648221147917
|View full text |Cite
|
Sign up to set email alerts
|

Long Sleep Duration Increases the Risk of All-Cause Mortality Among Community-Dwelling Older Adults With Frailty: Evidence From NHANES 2009–2014

Abstract: Objectives: The aim of this study was to determine the effect of sleep duration on all-cause mortality among older adults with frailty. Methods: The prospective cohort study included 5705 community participants aged 60 or above in the National Health and Nutrition Examination Survey (NHANES). Health indicators were selected in the NHANES to obtain the frailty index and sleep duration. The risk of all-cause mortality was estimated by a Cox proportional hazard model. Results: During the follow-up, long sleep dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 45 publications
0
0
0
Order By: Relevance
“…Existing studies of sleep duration on frailty in older adults have shown a nonsigni cant association between short sleep duration and risk of frailty [48], with only excessive sleep duration being signi cantly associated with a high risk of cognitive frailty [49]. This may be attributable to the U-shaped relationship observed between sleep duration and all-cause mortality, wherein the lowest risk is associated with a sleep duration of 5.8 hours from sleep onset [50].…”
Section: Introductionmentioning
confidence: 99%
“…Existing studies of sleep duration on frailty in older adults have shown a nonsigni cant association between short sleep duration and risk of frailty [48], with only excessive sleep duration being signi cantly associated with a high risk of cognitive frailty [49]. This may be attributable to the U-shaped relationship observed between sleep duration and all-cause mortality, wherein the lowest risk is associated with a sleep duration of 5.8 hours from sleep onset [50].…”
Section: Introductionmentioning
confidence: 99%